NEWLY CREATEDPROPAGATION OF CITRUS SEEDLINGS IN A SHORT TERM (British Journal of Global Ecology and Sustainable Development, 2024)
Experiments have shown that the vegetative method of preparing young seedlings from green cuttings is the most effective way to propagate newly created citrus cuttings. A newly created citrus seedling grown from cuttings grows normally, retaining all the genetic traits of the mother plant. For example, it was observed in the experiments that the newly created varieties of mandarin Mediana, lemon New Tashkent and ToshDAU begin to harvest in the second or third year after being transplanted into a seedling place made from cuttings, and give abundant harvest every year. The method of propagation of newly created citrus plants from cuttings is not difficult. Experiments have shown that if the temperature of the greenhouse is maintained at the same level, it is possible to continue taking cuttings from newly created citrus plants from February to September. But the best time is the beginning of May.